2019
DOI: 10.1016/j.compstruct.2019.111252
|View full text |Cite
|
Sign up to set email alerts
|

Using passive and active acoustic methods for impact damage assessment of composite structures

Abstract: This study aims to use the passive and active acoustic-based health monitoring methods for impact damage assessment of composite structures. To this aim, a Carbon Fiber Reinforced Polymer (CFRP) composite plate was fabricated and subjected to a simulated low-velocity impact by performing repeated quasi-static indentation tests where a loading-unloading-reloading test profile with 5 repetitions was adopted. Two Acoustic Emission (AE) broadband sensors and a network of eight piezoelectric (PZT) sensors were atta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 53 publications
(25 citation statements)
references
References 35 publications
(35 reference statements)
0
19
0
Order By: Relevance
“…Thus, in both cases the time can be determined by applying the threshold technique, only the determination of the healthy state and the corresponding reference value must be determined for each individual laminate. In summery, the complete failure detection in static test scenarios is going hand in hand with the results of the literature using carbon fibre-reinforced plastic [ 39 , 42 , 43 , 44 ], while the dynamic results going along with the results from Saeedifar et.al [ 45 ]. Consequently, the hypotheses H1 and H4 are confirmed, as it has been sufficiently demonstrated that both the damage index I and the standard deviation of the SED are applicable to determine the time of complete failure.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, in both cases the time can be determined by applying the threshold technique, only the determination of the healthy state and the corresponding reference value must be determined for each individual laminate. In summery, the complete failure detection in static test scenarios is going hand in hand with the results of the literature using carbon fibre-reinforced plastic [ 39 , 42 , 43 , 44 ], while the dynamic results going along with the results from Saeedifar et.al [ 45 ]. Consequently, the hypotheses H1 and H4 are confirmed, as it has been sufficiently demonstrated that both the damage index I and the standard deviation of the SED are applicable to determine the time of complete failure.…”
Section: Discussionmentioning
confidence: 99%
“…AE technology, successfully used in damage monitoring of fiber reinforced polymer composite materials (Boominathan et al., 2014; De Rosa et al., 2009; Fotouhi and Ahmadi Najafabadi, 2014; Gutkin et al., 2011; Hao et al., 2019; Refahi Oskouei et al., 2012; Saeedifar et al., 2015; 2018; 2019; Xu et al., 2020; Zhang et al., 2019b), was also applied in this study to monitor the progressive failure events during CAI process, by detecting rapid strain energy release due to microstructural damage producing transient elastic waves (Huguet et al., 2002; Serrano and Fabio, 1996). The AE acquisition parameters of multi-channel monitoring system AEwin manufactured by the Physical Acoustic Corporation set in the tests were as follows: threshold 45 dB, total gain 40 dB, Peak definition time (PDT) 20 μs, Hit definition time (HDT) 100 μs, Hit lockout time (HLT) 300 μs and maximum duration 100 ms. Two sensors (NANO-30) were securely attached to surfaces of the composite specimen by insulating elastic bandages, with silicone oil used as the coupling agent for enhancing the sensing effect.…”
Section: Methodsmentioning
confidence: 99%
“…To this aim, among structural health monitoring (SHM) techniques, acoustic emission (AE) technique has shown excellent potential for fully characterizing these damage mechanisms in laminated composites, i.e. damage initiation detection, damage identification, damage severity assessment, and damage localization [2][3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%